Enter evaluation of mitral inflow velocity profile: optimal through plane location for mitral inflow assessment with cardiac magnetic resonance - Mohd Shah, Azarisman Shah; Dennis, T. Wong; Richardson, James D; Li, Andrew; Adam, Nelson J.; Shirazi, Mitra; Bradley, Julie; Teo, Karen S; Worthley, Matthew; Worthley, Stephen G. (Pulsus Group, 2014)
Diastology is usually assessed using transthoracic echocardiography (TTE). Velocity‐encoded phase‐contrast imaging permits evaluation with cardiac magnetic resonance (CMR). Heterogeneous contour locations have been used to measure mitral (MV) inflow velocities and the optimal contour location is uncertain. We evaluated CMR MV inflow velocities against TTE to identify the optimal location.